Educational hazards? The politics of disaster risk education in Rio de Janeiro. Issue 1 (6th April 2020) - Coates, Robert
Abstract : Disaster education outcomes are highly dependent on the political context of that education. Based on a rich, in‐depth case study of the creation of community monitors in a landslide and flood‐prone city in southeast Brazil, this paper demonstrates how developmental and political environments add much additional nuance to existing theories of behaviourist and transformative education for disaster preparedness and mitigation. Beyond identifying the benefits of education, it argues that disaster risk reduction outcomes are reliant on governance frameworks that alter over time. The study reveals the political complexity associated with programme implementation and cites the perspectives of a number of participants. Disaster education is shown to be the necessary yet underappreciated twin of the militarised and technical approaches that dominate disaster response in Brazil. Understated, however, is education's situatedness: how it can become an arena of conflict between government and civil actors over matters of state and society in increasingly hazardous urbanisation settings in Latin America.